Peran Pemerintah Daerah Dalam Pelaksanaan Program Jaminan Sosial Rakyat Banten Bersatu (Jamsosratu) Berdasarkan Peraturan Gubernur Banten Nomor 15 Tahun 2019 Tentang Perubahan Atas Peraturan Gubernur Banten Nomor 10 Tahun 2019 - Annisak Hidayatiningtias (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
Social security the people Banten united in banten (Jamsosratu) is one of the programs protection and social insurance the government Banten to ensure the people who come from the households medium not capable of down based on the data PPLS/PBDT that have been validated and verified as RTS and make social assistance conditional cash. This study will discuss the role of the Banten Province Social Service in the implementation of the United Banten People's Social Security Program (Jamsosratu) based on Banten Governor Regulation Number 15 of 2019? and what are the obstacles faced by the Banten Provincial Social Service in implementing the social security program for the people of Banten united (Jamsosratu)? The research method used is juridical empirical based on qualitative juridical analysis sourced from primary data and secondary data. Primary data based on interviews obtained at the Social Service of Banten Province. Secondary data is based on primary legal material data, and theoretical studies based on expert opinions, as well as qualitative data showing the implementation of Jamsosratu in Banten Province. This research found that the role of the Banten Provincial Government in implementing the Jamsosratu program was to make policies, regulations, guidelines and provide a budget for Jamsosratu implementation. The Banten Provincial Social Service is one of the authorized agencies to implement the Jamsosratu program management in Banten Province. Several factors that influence the management of the Jamsosratu program are divided into three factors, namely the completeness of community data, the coordination factor between the institutions concerned, and the lack of public understanding of the existence of Jamsosratu.